PERILAKU KELUARGA PETANI DALAM PENGANEKARAGAMAN KONSUMSI PANGAN BERDASARKAN KARAKTERISTIK KELUARGA DI KELURAHAN BARU LADANG BAMBU KECAMATAN MEDAN TUNTUNGAN TAHUN 2015 - Faradilla .; Jumirah .; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Diversification of food consumption is effort to stabilize consumption patterns to fit of Dietary Pattern Expectations. The purpose of this research is to determine behavior of farmers family in diversification of food consumption based on the characteristics of families in Baru Ladang Bambu District, Medan Tuntungan Subdistrict in 2015. This was a descriptive research with cross sectional study design. Population were a whole family of farmers in Baru Ladang Bambu District, Medan Tuntungan Subdistrict, sampling was done with the proportional random sampling were 63 farmers. Primary data were collected through interviews using a form of inventory method. The result showed that the diversification of food consumption majority of farm families with high category (≥6 food group), knowledge of the majority of the good category and the attitude of the majority of good category, while diversityfood consumption based on the characteristics of family farmers, land ownership is in the category of landless, education level housewife in junior high school category, income <Rp.2.037.000 and the number of family members ≤4 people. Based on the result of this research, expected to the subdistrict officer to make a cooperation with the Department of Agriculture and Food Security to further improve guidance to farm families with focus outreach efforts about diversification of food consumption. Keywords: family behavior, diversification of food, family characteristics